MENGULAS NOVEL REMAJA MENGGUNAKAN MODEL PEMBELAJARAN THINK PAIR SHARE PADA SISWA SMPN 2 MALANG - Indra Sulistyaningrum (Center of Language and Cultural Studies, 2017)
This study aims to improve the accomplishment to review teenager novel using the learning model of Think Pair Share. This study used classroom action research design with two cycles. The research subject was the eighth graders of SMP Negeri 2 Malang in the academic year 2013/2014 consisting of 32 students. This classrom action research applied four step cycle: planning, acting, observing and reflection. Data were collected using observation and interview and the data were analyzed using descriptive statistics. The results of the study showed that: attainment in the cycle I of this study was: average score 74.73 and the mastery learning 72%. In the second cycle, the results were the average score as 84.53 and the mastery learning 98%. The results of questionnaire evidently showed that the students were happy to learn using Think Pair Share and they enjoyed following the learning processes.